The role of critical mineral prices and geopolitical risk in shaping renewable energy poverty - Wen Hui Lee; Dzul Hadzwan Husaini; Hooi Hooi Lean; Ghee-Thean Lim (Discover Sustainability)
Abstract Renewable energy poverty is a serious challenge for BRICS+ nations due to large geographical areas and uneven population distributions. Energy transition efforts in the bloc are further undermined by soaring prices of renewable technologies due to rising critical mineral costs. Simultaneously, the increasingly complicated geopolitical environment caused by recent geopolitical events, such as the Russia-Ukraine conflict and USA-China trade war, has further exacerbated the challenges of energy transition in the bloc by increasing uncertainty in the global energy and critical mineral markets. The combined effects of surging critical mineral costs and growing geopolitical risks hinder a fair and sustainable energy transition in the BRICS+ countries. Nevertheless, the subtle relationship between critical mineral prices, geopolitical risks, and renewable energy poverty remains underexplored. This paper extends the current literature by examining the indirect relationship between disaggregated critical mineral prices, geopolitical risks, and renewable energy poverty among BRICS+ nations. This study applies the two-step system generalized method of moments (GMM) estimator for the period 2012–2022. The findings show that zinc and cobalt prices have direct negative effects on renewable energy poverty. In terms of an indirect relationship, geopolitical risks significantly moderate the relationship between all selected critical mineral prices and renewable energy poverty. As a policy response, BRICS+ members should strengthen their critical mineral supply chain by boosting intra-bloc trade and diversifying trading partners outside the bloc. Besides, BRICS+ countries should promote cross-border research collaborations to reduce critical mineral intensity in renewable technologies to build a resilient renewable energy ecosystem against geopolitical tensions and external dependence.